Integration of White-Tailed Deer Herd Improvement with Management of Private Forest Land in Wisconsin - Vanderhoof, Robert E. (University of Wisconsin-Stevens Point, College of Natural Resources, 1986)
Following a large die-off of white-tailed deer (Odocoileus virginianus) on Chambers Island, Wisconsin in 1979, the island landowners sought technical assistance in managing the island to increase the quality (i.e. body-size and antler development) of the deer herd and promote regeneration of desireable hardwood timber species. Morphological data from island deer during 1980-1983 (N = 91) showed they were substandard in quality to those from adjacent mainland Door County (N = 300) or 8 other management units in Central Wisconsin (N = 390). A founder effect was hypothesized and investigated using horizontal starch-gel electrophoresis of 5 enzyme systems present in the major organ and skeletal muscle tissues of the island (N = 50) and mainland Door County deer (N = 250). Genotypic and allelic frequencies, and mean single locus (ho) and mean total (Ho) heterozygosities exhibited significant locational differences, however no founder effect was noted. A possible link between population genetics and population dynamics of white-tailed deer populations is discussed. Vegetation analysis on Chambers Island revealed a lack of northern red oak regeneration and an impoverished and unstable white-tailed deer winter food base. Mast accounted for 83% of the island's winter carrying capacity. An integrated management plan stabilizing the winter food base while regenerating desireable northern hardwood tree species is proposed. A harvest plan designed to increase the quality of the island deer herd was implemented in 1982. Positive results of the harvest plan have already been noticed (confirmed presence of at least 1 12-point and 5-8 a-point bucks on the island in 1983). Modifications of the present harvest regulations are proposed.